Cascaded Heterogeneous Simulations for Analysis of Mechatronic Systems in Large Scale Transportation Scenarios - Hassan, Bassem; Wassmann, Helene; Klaas, Alexander; Kessler, Jan Henning (Proceedings of the 2012 Emerging M&S Applications in Industry & Academia Symposium, Spring Simulation Multiconference,)

Ensuring calls to automotive suppliers with minimal costs with special consideration of liquidity {\ "a} ts-, Besch {\ "a} qualification, know-how and IT restrictions - Delius, Robin

A Cross-Level Approach To Planning Changeability in Distribution Systems - Klingebiel, Katja; Winkler, Matthes; Klaas, Alexander; Laroque, Christoph (Proceedings of the 2012 Emerging M&S Applications in Industry & Academia Symposium, Spring Simulation Multiconference)

Effektives Customer Relationship Management: Instrumente - Einführungskonzepte - Organisation - Helmke, Stefan, Stefan; Uebel, Matthias; Dangelmaier, Wilhelm

Credit risk securitization and bank soundness: Evidence from the microlevel for Europe - Michalak, Tobias C.; Uhde, André (Quarterly Review of Economics and Finance)
Using a unique sample of 749 cash and synthetic securitization transactions issued by 60 stock-listed bank holdings in the EU-13 plus Switzerland over the period from 1997 to 2007 this paper provides empirical evidence that credit risk securitization has a negative impact on the issuing banks’ financial soundness. Baseline findings hold even when controlling for likely reverse causality by employing instrumental variable techniques and substituting the accounting-based z-score ratio by market-based indicators of bank risk. Moreover, investigating the relationship between credit risk securitization and single z-score components in order to evaluate significant transmission channels proposed by relevant theoretical literature, we find a negative impact of securitization on bank profitability and capital environment as well as a positive relationship between securitization and the issuing bank's return volatility. Against the background of our empirical results we underline that the decision by the Basel Committee to enhance the new Basel III framework in the field of securitization is a step in the right direction.
Keywords: Credit risk securitization Bank soundness European banking

Cross-border bank lending - Empirical evidence on further determinants from OECD banking markets - Müller, Oliver; Uhde, André (Journal of International Financial Markets, Institutions & Money)
Employing data on foreign bank claims from 13 OECD countries on 51 emerging markets between 1993 and 2007, this study investigates specific characteristics of OECD banking markets and lending banks as new important determinants of cross-border lending. We initially provide empirical evidence that in addition to well-accepted “gravity measures”, characteristics of OECD banking markets as well as lending banks’ attributes may describe further important determinants of cross-border bank lending with regard to our sample. Building subsamples of more-developed emerging markets vs. frontier markets, addressing (non) common lender relationships and analyzing cross border lending flows during different time periods, our analysis additionally reveals that both the determinants’ explanatory power and their direction of impact notably vary with respective subsamples.
Keywords: Foreign bank claims; Gravity measures; OECD banking markets’ characteristics; Lending banks’ characteristics

Wealth effects of credit risk securitization in European Banking - Farruggio, Christian; Michalak, Tobias C.; Uhde, André (Journal of Business Finance and Accounting)
Using a unique cross‐sectional dataset of 381 cash and synthetic securitizations issued by 53 banks from the EU‐15 plus Switzerland between 1997 and 2007, this paper provides empirical evidence for time‐dependent negative wealth effects of credit risk securitization announcements in European banking. Baseline results hold when comparing estimated wealth effects with a control group of similar but non‐securitizing banks for the relevant time period. Moreover, building several sub samples we find that the nexus between credit risk securitization, the issuing banks’ overall risk exposure and wealth effects is associated with a variety of transaction‐ and bank‐specific factors.
Keywords: wealth effects; credit risk securitization; Europe; event study

Measuring the quality of banking supervision revisited - Assessments by German banks before and during the financial crisis - Paul, Stephan; Stein, Stefan; Uhde, André (Journal of Governance and Regulation)
This contribution presents and discusses main results of a new survey on the assessment of supervisory quality among German banks in 2010. In particular, it is analyzed if and how supervised banks’ perception of the quality of supervisory authorities and their instruments has changed due to the financial crisis starting in mid-2007. Subsequently, results from the recent survey are compared with findings provided by a former study carried out by the authors in 2006 (Paul, Stein and Uhde, 2008).
Keywords: banking supervision; quality; assessment; banking sector

Sovereign Risk and Bank-Specific CDS Pricing - Meine, Christian; Michalak, Tobias C.; Uhde, André
Employing time series of single-name CDS market spreads from 29 European banks located in the EU-12 plus Switzerland and the UK over the period from January 2004 through September 2010 this paper analyses the relationship between increasing sovereign risk and bank-specific CDS pricing. Results from calculating relative CDS spread deviations (model minus market spreads) initially reveal a price bubble in the European CDS market until the beginning of the financial crisis in mid-2007. From this point in time the gap narrows remarkably during the financial crisis and sovereign debt crisis period. Corresponding to these findings, the empirical analysis reveals a negative impact of sovereign risk on calculated CDS spread differentials indicating a spill-over effect between sovereign risk and bank risk and hence, a positive effect on bank-specific CDS pricing. Further analyses reveal that the perception of sovereign risk is not crisis- but country-dependent suggesting that bank-specific CDS market spreads may already include a premium to cover sovereign risk from PIIGS countries during the pre-crisis period in Europe.
Keywords: Sovereign risk; Structural credit risk models; bank-specific CDS pricing

Wertorientierte Vergütung des Aufsichtsrats - Auswirkungen auf den Unternehmenswert - Ebert, Michael; Zein, Nicole (Betriebswirtschaftliche Forschung und Praxis)

Der Einfluss der Zinsschranke auf unternehmerische Kapitalstrukturentscheidungen - Maßbaum, Alexandra; Klotzkowski, Tasja; Sureth-Sloane, Caren (Zeitschrift für Betriebswirtschaft)

Does insider shareholding matter to corporate payout reactions to tax reforms? - Sureth-Sloane, Caren (Zeitschrift für Betriebswirtschaft)

Editorial: What Is and What Is Not a Substantial Contribution? - Albers, Sönke; Sureth, Caren (Business Research)

I thought it was all over and now it is back again – Customer reactions to time extensions of sales promotions - Garnefeld, I.; Münkhoff, Eva; Bruns, A. (2012 AMA Summer Academic Conference, Chicago, IL)

Growing with industrial services – A configurational approach (ausgezeichnet mit Best Paper Award) - Eggert, A.; Münkhoff, Eva; Thiesbrummel, C. (2012 AMA Winter Academic Conference, St. Petersburg, FL)

Die Messung von Joint-Venture-Erfolg - Isidor, Rodrigo; Schwens, Christian; Kabst, Rüdiger (Markteintrittsstrategien)

Die Messung von Joint-Venture-Erfolg - Isidor, Rodrigo; Schwens, Christian; Kabst, Rüdiger (Markteintrittsstrategien)

Die Messung von Joint-Venture-Erfolg - Isidor, Rodrigo; Schwens, Christian; Kabst, Rüdiger (Markteintrittsstrategien)

Determinants of different types of born globals - Baum, Matthias; Schwens, C.; Kabst, Rüdiger (Handbook of Research on Born Globals)

Determinants of different types of born globals - Baum, Matthias; Schwens, C.; Kabst, Rüdiger (Handbook of Research on Born Globals)